2021
DOI: 10.1155/2021/9986498
|View full text |Cite
|
Sign up to set email alerts
|

The Correlation between Dental Stages and Skeletal Maturity Stages

Abstract: Introduction. The determination of skeletal maturity stages is very important in orthodontic treatment planning, especially skeletal discrepancies in growing individuals. A hand-wrist radiograph is considered the most accurate approach for skeletal maturity detection. Dental calcification stages have been suggested as an alternative diagnostic method to decrease radiation exposure. The recent study is aimed at detecting the efficacy of dental calcification stages in assessing skeletal maturity during the prepu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 39 publications
(45 reference statements)
0
9
0
Order By: Relevance
“…for title and abstract. Out of these, we included 25 papers for full-text screening [22][23][24][25][26][27][28][29][30][31][32][33][34][35][36][37][38][39][40]. Six articles not respecting eligibility criteria were excluded by the systematic review.…”
Section: Resultsmentioning
confidence: 99%
“…for title and abstract. Out of these, we included 25 papers for full-text screening [22][23][24][25][26][27][28][29][30][31][32][33][34][35][36][37][38][39][40]. Six articles not respecting eligibility criteria were excluded by the systematic review.…”
Section: Resultsmentioning
confidence: 99%
“…According to Günen Yılmaz et al (2019) tooth calcification stages of mandibular second premolars showed the highest positive correlation with skeletal maturation stages. In a study evaluating skeletal and dental maturation (Jourieh et al, 2021), it was determined that 76.66% of girls and 86.66% of boys at the MP3cap stage had mandibular second molars at the G stage. In our study, the number of individuals with mandibular second molar teeth in the G stage was higher compared to the other stages, and there was a significant but low correlation between the cervical vertebra and mandibular second molar tooth development stages in both sexes.…”
Section: Discussionmentioning
confidence: 99%
“…6 Multitudinous studies have been conducted to evaluate correlation between different skeletal age predictors. [7][8][9][10][11][12][13][14][15][16][17] The results vary from population to population thereby escalating the need for more research in individual populations. The current study was carried out to explicate the association between the lower second molar calcification stages and cervical vertebral maturation stages in patients of Southern Punjab population of Pakistan.…”
Section: Discussionmentioning
confidence: 99%